Assessment in the zone of proximal development: simulator-based competence tests and the dynamic evaluation of knowledge-in-action. Issue 4 (2nd October 2022) - Sellberg, Charlott; Lundin, Mona; Säljö, Roger
ABSTRACT: The background of this article is an interest in analysing how assessment of professional skills is conducted in higher education contexts, drawing on video data from a course on maritime navigation. The empirical study focuses on a) how students working in a bridge simulator are able to display their knowledge about how to calculate the relation between rate of turn, turn rate and speed when navigating, and b) how their performance is evaluated. The results show that the dynamics of the assessment situation and the interaction between the student and the assessor are decisive in how well students manage the task. When analysing assessment of a professional skill as a concrete practice, knowledge emerges through joint work and cannot be ascribed to the student only. At one level, this may be seen as a threat to the validity of the testing situation, but from a different perspective, the display of knowledge-in-action is always responsive to what happens in the exercise of a professional skill.